Мікроконтролерна система для аналізу швидкісних характеристик велосипеду - Чистяков, Д. Ю. (ХНУРЕ, 2025)
The paper presents the development of a microcontroller-based system for analyzing bicycle speed characteristics using ESP8266. The system integrates a Hall sensor for speed measurement, LED indicators with brake signaling, and Wi-Fi communication with a mobile application. The research focuses on creating an energy-efficient solution with real-time data processing capabilities. The developed system provides accurate speed and distance measurements, trip history storage, and customizable settings through a convenient mobile interface. The proposed solution offers significant advantages over existing commercial bike computers in terms of functionality and cost-effectiveness.
Keywords: велосипед; bicycle speed